Optimalisasi Badan Penyelesaian Sengketa Konsumen (BPSK) dalam Upaya Proteksi Hak Konsumen di Ranah Siber - Maudy Andreana Lestari; Dewi Ari Shia Wase Meliala; Puja Anudiwanti; Nasya Nurul Amalina (CV Rewang Rencang, 2021)
Nowadays, the internet is being used as a platform to transact digitally which brings along new responsibilities for Indonesian law to protect consumers from online transaction frauds. Unfortunately, the existence of The Consumer Dispute Settlement Agency (BPSK) now hasn’t been considered as effective due to the lack of rights it has. Hence, the result of this study will show what BPSK needs to do to optimize its role in protecting cyber consumers, which are implementing Online Dispute Resolutions (ODR) and updating regulations that covers more of cyber consumer's rights.